Pengembangan Panduan Bimbingan Keterampilan Kerjasama Berbasis Permainan Tradisional Balbudih untuk Siswa SMP - Agus Dwi Setyawan; Siti Hartinah (Institut Agama Islam Negeri Kerinci, Indonesia, 2019)
The objectives in this study consist of 2 specific objectives, namely (1) general objectives, namely to produce guidance guidelines on cooperation skills based on Balbudih Traditional Games for junior high school students. And, (2) specific objectives namely (a) to produce guidance on cooperation skills that meet acceptability carried out through expert testing and prospective user testing, (b) to produce guidance guidelines based on traditional Balbudih games that are effective for enhancing cooperative skills. This research is a research development of the Borg and Gall model that examines the development of guidelines for cooperation skills based on the Traditional Balbudih Games for junior high school students. Small group trial subjects were conducted on 12 junior high school students. This study uses data collection techniques namely observation, interviews and questionnaires. The results of the study show that: (1) the results of developing guidelines for the guidance of cooperation skills based on the Traditional Balbudih Games for junior high school students have met the acceptability criteria which are carried out through expert tests and prospective user tests. (2) Producing guidance guides based on traditional Balbudih games which are effective for improving the cooperation skills of junior high school students